A decade of incurred sample reanalysis: failures, investigations and impact. (10th October 2018) - Lee, Lisa B; Wickremsinhe, Enaksha R
Incurred sample reanalysis (ISR) is used to ensure the validity and reliability of bioanalytical data. Additionally, ISR results also help identify issues that could influence or bias the data. Overall, based on a decade of experimental data generated at Eli Lilly and Company, ISR failures are few with less than 5% of ISR samples failing to meet acceptance criteria. In a majority of situations, the cause for ISR failures has been 'human-error.' However, there are examples where ISR has helped identify issues related to the stability of the analyte or the ruggedness of the method. As a strategy, it is beneficial to conduct ISR following the completion of a few sample runs, so any potential issues impacting the validity and reliability of the data can be identified and rectified early.